P319 Impact of biological agents on postoperative complications in inflammatory bowel disease: a multicentre study of GETECCU. (27th May 2021) - García García, M J; Rivero, M; Miranda-Bautista, J; Bastón-Rey, I; Mesonero, F; Leo-Carnerero, E; Casas-Deza, D; Cagigas Fernández, C; Martin-Cardona, A; El Hajra, I; Hernández-Aretxabaleta, N; Pérez-Martínez, I; et al.
Abstract: Background: It has been suggested that biologic therapy may increase the risk of postoperative complications in inflammatory bowel disease (IBD), but the evidence is scarce. Our aim was to evaluate whether the treatment with anti-TNF agents, ustekinumab or vedolizumab increase the risk of complications after surgery. Methods: IBD patients undergoing intra-abdominal surgery between 1 st January 2009 and 31 st December of 2019 were retrospectively selected. Data collection included clinical characteristic of IBD, biochemical parameters and surgical aspects. Postoperative complications (PC) were defined as those occurring within 30 days after surgery. Exposed cohort (EC): Patients who received the last dose of the biologic within 3 months before surgery. Non-exposed cohort (NEC): Patients who did not receive biologic treatment within 3 moths prior to surgery. Predictive factors for PC and for infections were identified by logistic regression analyses. A genetic matching score was performed to balance the clinical characteristics of both groups. Results: A total of 1, 535 surgeries performed in 37 centres were included: 81% in Crohn's disease, 18% in ulcerative colitis and 1% in unclassified-IBD patients. A total of 711 surgeries (46.3%) had been exposed to biologics (583 under anti-TNF therapy, 58 under vedolizumab and 69 under ustekinumab) and 824 surgeries (53.7%) the NEC. PC were reported in 38% (n=267) of patients in the exposed cohort and in 34% (n=280) of patients in the non-exposed one (p=0.15), including dehiscence, infection, obstruction, ileus, bleeding, thrombosis, fistula and evisceration. The most frequent complications were infections (48% of all the cases). A 30-day hospital readmission was needed in 7% (n=110) of the patients, and 2% (n=29) required a new surgery with no differences (p>0.05). Multivariate analysis for PC and infections is presented in table 1. The frequencies of PC for each biologic in the univariate analysis are represented in figure 1. No specific treatment was associated to PC or infections in multivariate analysis. Conclusion: Preoperative administration of biological therapy does not seem to be a risk factor for overall PC, although it may be for postoperative infections.